Uji Aktivitas Antelmintik Ekstrak Etanol Kulit Batang Sengkuang Dracontomelon dao (Blume) Merr. & Rofle Terhadap Cacing Gelang Ayam (Ascaridia gallu) Secara In Vitro - Inderiyani Inderiyani; Heny Puspasari; Risma Wahyu Architasari (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
Worms are diseases caused by worms that need serious treatment. Sengkuang Dracontomelon dao (Blume) Merr & Rofle has the potential as an alternative worm treatment because it contains secondary metabolites i.e. alkaloids, saponins, tannins, flavonoids and triterpenoids which have activity as anthelmintics. This study aims to determine the activity, LC50 and LT50 values ​​of sengkuang stem bark as an anthelmintic against Ascaridia galli in vitro. Sengkuang bark is processed into simplicia and then macerated using 96% ethanol as a solvent. Then the extract was used to test the anthelmintic activity by incorporating 5 chicken roundworms into each test solution, 0,9% NaCl (negative control), 0,5% mebendazole (positive control), ethanol extract of sengkuang stem bark 0,2%; 0,4%, and 0,6%. Incubated at 37°C and observed the time of paralysis, the time and number of worm deaths every 1 hour for 24 hours. The results showed that the ethanol extract of sengkuang bark at concentrations of 0,2%; 0,4% and 0,6% had anthelmintic activity with a mortality rate of 100%, an LC50 value is 0,13% and an LT50 value respectively is 15,67 hours; 10,83 hours and 7,85 hours.